Wybrane charakterystyki kapitału ludzkiego polskich obszarów wiejskich - Spychalski, Grzegorz (Selected Features of Polish Rural Areas Human Capital, 2005)
The work is an attempt of human capital quality analysis in the Polish rural areas in the aspect of the economic progress. There is the description of selected features of the Polish rural areas households with the special consideration of education structure and sources of income identification. Then there is a thesis of key role of human capital development in socioeconomic structure detrmination. As the conclusion of the work one can find elements of economic policy program of state and local authorities facilitating enterpreneurship development as well as civilisation headway of the rural areas in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 290-296